Evaluation of two different vacuum-assisted breast biopsy systems: Mammotome® system 11G/8G vs. ATEC® system 12G/9G. (March 2013) - Order, Berndt-Michael; Schaefer, Philipp J; Peters, G; Eckmann-Scholz, Christel; Hilpert, Felix; Strauss, Alexander; Warneke, Viktoria; Mathiak, Micaela; Heller, Martin; Jonat, Walter; Schaefer, Fritz KW
Background: Breast cancer screening programs have been established worldwide and early detection of breast cancer has increased steadily. The most common way to confirm dignity of non-palpable and sonographically-occult suspicious findings on mammography is the stereotactically-guided vacuum-assisted breast biopsy Purpose: To compare two stereotactically guided vacuum-assisted breast biopsy systems measuring time effectiveness and quality of harvested material in clinical practice. Material and Methods: One hundred and forty-six patients presenting with suspicious microcalcifications on mammography were included in the study. Biopsies were carried out with either the Mammotome ® system (11-gauge and 8-gauge) or the ATEC ® system (12-gauge and 9-gauge). Lesions with a diameter <15 mm on mammography were biopsied with 11-gauge or 12-gauge devices whereas lesions >15 mm were targeted with 8-gauge and 9-gauge. Mammotome ® system 8-gauge device was used in 34 patients, the 11-gauge system in 37 patients. The ATEC ® system 9-gauge system was used in 37 patients and 12-gauge in 38 patients. Time was taken, focusing on preparing the system, time of collecting the samples, preparing the samples, and cleaning the site. During the biopsies 24 samples were taken. The histologic quality of the tissue samples was judged by a pathologist in a blinded fashion according to a specimen grading classification concerning tissue fragmentation, artefacts, and the adequacy of the tissue for diagnosis. Results: The median overall time for the Mammotome ® system was 879 s (11-gauge) and 934 s (8-gauge) and for the ATEC ® system 671 s (12-gauge) and 673 s (9-gauge). The ATEC ® system displays a significantly shorter overall time for small and large biopsy devices (U-test, P < 0.001). Concerning the mean time difference of the overall time comparing small and large systems the ATEC ® system was 267.6 s faster using the small and 244.8 s faster using the large system. Comparing the histologic quality of tissue samples the Mammotome ® system shows significantly higher values for the large and the small system (Chi-square test, P < 0.001). Conclusion: Both biopsy systems meet all requirements for daily practice and confirm the diagnosis of suspicious microcalcifications. The ATEC ® system was observed to be faster but this difference of about 250 s might not be relevant in daily practice. The Mammotome ® system provides a better histologic quality of tissue samples.